Inventive activity of Scientific Center of Reconstructive and Restorative Surgery SB RAMS (report 1) - L. A. Valerius; K. A. Apartsin (Acta Biomedica Scientifica)
The article presents the review of inventive and patent work of employees of Scientific Center of Reconstructive and Restorative Surgery SB RAMS from the foundation of institute of surgery till nowadays. Main areas of researches (in the form of patents) are determined: prevention and treatment of surgical infection, methods of treatment of actual surgical pathology of neck, chest, abdomen and soft tissues and also instrumental and laboratory diagnostics of these conditions. The models of pathological processes developed in experiment and cell technologies are patented. The level of patent defense of researches is considered to be corresponding.